Analisis Tingkat Pemahaman Dan Penerapan Pengelolaan Limbah B3 Pada Bengkel Motor Di Kota Makassar - Aminuddin, Aminuddin; Z, Muhsin; Romadin, Achmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
Hazardous and toxic (B3) waste management is an important aspect in preserving the environment and public health in urban areas, as this waste includes a variety of materials that can cause serious damage if not managed properly. The research method used is mixed method, using data collection interviews, observation, documentation and questionnaire studies. Based on the research results obtained: (1) knowledge of hazardous waste in Makassar city motorcycle repair shops shows quite good results with an average value of 4.15 which falls into the